Explaining Criteria of the Adaptive Model for Commercializing Academic Research with a Knowledge-based Employment Development Approach in the Health System - Mohammadi Zaer, Sara; Anjomshoaa, Zahra; Salajegheh, Sanjar; Nazari, Akbar; Pour Rashidi, Rostam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aimed to design and validate a model for commercializing academic research with an approach focused on the development of knowledge-based employment within Iran’s health system. Methodology: The research method was applied-developmental in terms of its goal and descriptive-survey in nature. The statistical population included experts in the field of academic research commercialization and faculty members from medical universities in Iran. In this phase, seven commercialization experts and senior managers from the Vice-Presidency for Science, Technology, and Knowledge-based Economy, along with five academic experts in management, were selected. Theoretical sampling was used to select participants, continuing until theoretical saturation was achieved. Data were simultaneously collected and coded. Findings: The designed model, based on grounded theory, was formulated into a questionnaire and distributed among 400 research center managers, faculty members, and senior managers of the aforementioned universities. Data collection in the qualitative section was conducted through interviews. Grounded theory was utilized for data analysis in the qualitative section. The results indicated that the model for commercializing academic research with an approach to developing knowledge-based employment within the health system is valid and desirable. Conclusion: Commercializing academic research in the medical and health domain plays a fundamental role in advancing economic growth and creating knowledge-based employment. By bridging the gap between academia and industry, universities can transform scientific discoveries into innovative products and services that address critical healthcare needs while stimulating economic growth.